2019
DOI: 10.1007/s00122-019-03385-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and assessment of two major QTLs for dwarf bunt resistance in winter wheat line ‘IDO835’

Abstract: Key message Two major dwarf bunt resistance QTLs were mapped to a known Bt9 locus and a novel locus. The associated KASP markers were developed and validated in other two populations. Abstract Dwarf bunt (DB), caused by Tilletia controversa J.G. Kühn, and common bunt (CB), caused by T. caries and T. foetida, are two destructive diseases that reduce grain yield and quality in wheat. Breeding for bunt-resistant cultivars is important in many wheat production areas, especially where organic wheat is grown. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 30 publications
7
34
1
Order By: Relevance
“…Two major QTL, Q.DB.ui-7DS (Chen et al 2016), Q.DB-6DL (Steffan et al 2017;Wang et al 2019) and Q.DB.ui-7AL (Wang et al 2019) that were previously reported in biparental populations, were not detected in this study. The QTL Q.DB.ui-7DS was reported in the 'Rio Blanco'/'IDO444' population on 7DS with a peak marker, wPt-2565, at 5.9 Mbp near the telomere (Chen et al 2016).…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Two major QTL, Q.DB.ui-7DS (Chen et al 2016), Q.DB-6DL (Steffan et al 2017;Wang et al 2019) and Q.DB.ui-7AL (Wang et al 2019) that were previously reported in biparental populations, were not detected in this study. The QTL Q.DB.ui-7DS was reported in the 'Rio Blanco'/'IDO444' population on 7DS with a peak marker, wPt-2565, at 5.9 Mbp near the telomere (Chen et al 2016).…”
Section: Discussioncontrasting
confidence: 62%
“…However, our GWAS did not detect any markers significantly associated with 6DL in any of the data sets. Using a biparental mapping population derived from a University of Idaho wheat breeding line 'IDO835', Wang et al (2019) found two QTL for DB resistance, one on 6DL corresponding with the Bt9 locus, and one on 7AL. We used the resistant haplotypes for both loci to find accessions that contain these QTL (Table 6, Supplementary File 9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bt10 was mapped to the short arm of chromosome 6D (Menzies et al 2006) and Bt9 was mapped by Steffan et al (2017) to the long arm of chromosome 6D. Both genes were validated in independent populations (Singh et al 2016;Wang et al 2019), and DNA markers linked to the genes have been published for the purpose of marker-assisted selection (MAS) of Bt9 (Steffan et al 2017;Wang et al 2019) and Bt10 (Laroche et al 2000;Menzies et al 2006). Bunt resistance is mediated partly by non-race specific quantitative trait loci (QTL), and 24 QTL for bunt resistance have been identified to date by QTL mapping in wheat.…”
Section: Introductionmentioning
confidence: 99%
“…A major QTL for DB resistance was identified by Chen et al (2016) on the short arm of chromosome 7D. Minor DB QTL were identified on 1A (Chen et al 2016), 2B (Chen et al 2016), and 7A (Wang et al 2019). Association mapping studies identified several significant marker traits association for CB.…”
Section: Introductionmentioning
confidence: 99%